2009
DOI: 10.1016/j.ijcard.2008.03.087
|View full text |Cite
|
Sign up to set email alerts
|

Cataloguing the geometry of the human coronary arteries: A potential tool for predicting risk of coronary artery disease

Abstract: Background-The nonuniform distribution of atherosclerosis in the human vasculature suggests that local fluid dynamics or wall mechanics may be involved in atherogenesis. Thus certain aspects of vascular geometry, which mediates both fluid dynamics and wall mechanics, might be risk factors for coronary atherosclerosis. Cataloguing the geometry of normal human coronary arteries and its variability is a first step toward identifying specific geometric features that increase vascular susceptibility to the disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…28 A case of quadruplets, whose parents were blood relatives, with the syndrome, suggests that it is an autosomal recessive disease. 29 …”
Section: Arterial Tortuosity Syndromementioning
confidence: 99%
“…28 A case of quadruplets, whose parents were blood relatives, with the syndrome, suggests that it is an autosomal recessive disease. 29 …”
Section: Arterial Tortuosity Syndromementioning
confidence: 99%
“…They run along the surface of the heart and are curved, bent, and angulated (Smith, et al 2001). In addition, it has been observed that plaque accumulation is related to vessel curvature, with plaque accumulating more rapidly in angulated vessels where wall shear stress is low (Wahle, et al 2006;Zhu, et al 2008). As a result, stents are most often placed in curved positions within the coronary arteries and remain in a bent position throughout their lifetime (Fournier, et al 2005;Smith, et al 2001).…”
Section: Published In Computer Methods and Programs In Biomedicine Bymentioning
confidence: 99%
“…From single and multiple vessel disease to bifurcated, angulated and long lesions, the variation and complexity of coronary artery disease and the advanced capabilities to detect and determine the extent and severity has led to an increased interest in intravascular device innovation (Zhu, et al 2008;Kini 2006). A variety of stent designs currently exist and continuous efforts are being made to improve both stent design and placement procedures (Kandzari, Tcheng and Zidar 2002;Kraitzer, Kloog and Zilberman 2008).…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations